Study on Medium-Thick Al-Alloy T-Joints by Dual P-GMAW Bilateral Synchronous Welding - Chunsheng Wang; Haicang Zhang; Zhaoyang Yan; Yun Zhao; Shujun Chen (Metals, 2021)
The T-joints of medium-thick 6082 Al-alloy plates created by dual pulsed gas metal arc welding (P-GMAW) and bilateral synchronous welding were investigated to improve weld quality using the adaptive deposition method, which calculates the minimum amount of deposition according to the welding condition, groove size, and cross-sectional area, effectively reducing the heat input and deformation of the welds on the basis of weld filling. The optimized linear energy with a wire feed speed (WFS) of 9.5 m/min can ensure a well-formed weld with a complete root fusion, and high-quality T-joint welds were obtained both in root openings of 0 mm and 1 mm. The biggest penetration was 4 mm, which was four times more than that of the result from a single torch welding process. When the distance between the two welding torches exceeded 20 mm, the molten pool was completely separated, and process pores were observed in the unfused root zone. Influenced by the thermal cycles in asymmetric welding, the hardness distribution changed: the width of the softer zone at the base plate with the fore arc was smaller than that zone with the rear arc. Furthermore, dual P-GMAW bilateral synchronous welding with an asymmetric heat source can further reduce the deformation of the welded joint by about 20% compared to that of symmetric welding.